Predictors of Clergy’s Ability to Fulfill a Suicide Prevention Gatekeeper Role - Mason, Karen (Journal of pastoral care & counseling, 2016)
Catholic, Jewish and Protestant clergy (n = 801) completed a survey to identify predictors of clergy’s ability to fulfill a suicide gatekeeper role. Exploratory backward stepwise regression identified predictors of risk identification including suicide knowledge, religion, conducting suicide funerals, having an attitude that people have a right to die, age, and race. Predictors of ability to intervene include suicide knowledge, training, religion, right to die attitude, and ethnicity. Recommendations include more suicide training and clergy self-care.